High VISTA expression is linked to a potent epithelial-mesenchymal transition and is positively correlated with PD1 in breast cancer - Rezouki, Ibtissam; Zohair, Basma; Ssi, Saadia Ait; Karkouri, Mehdi; Razzouki, Ibtissam; Elkarroumi, Mohamed; Badou, Abdallah (Frontiers in Oncology, 2023)
Breast cancer is the most common tumor in women worldwide. Immunotherapy has shown positive results after blocking of programmed cell death-1 (PD-1), PD-1 ligand-1 (PD-L1), and cytotoxic T-lymphocyte-associated protein 4 (CTLA-4) in breast cancer patients. However, many patients are resistant to this type of therapy. The search for new immune checkpoint targets is still required to overcome this limitation. The Ig suppressor of T cell activation domain V (VISTA) is a novel immune checkpoint that delivers inhibitory signals to T cells. This molecule has shown promising results in many cancer types. Our study highlighted the association of VISTA with clinicopathological parameters of breast cancer and its involvement in the Epithelial-Mesenchymal-Transition (EMT) process, as well as its correlation with PD1 expression. Transcriptomic analysis showed that VISTA is associated with ER and PR negative status and the TNBC molecular subtype. VISTA was also highly associated with an immunosuppressive microenvironment. Interestingly, protein analysis via immunohistochemistry corroborated these previous results, indicating that VISTA was expressed in most immune cells (94%) and that it was highly expressed in tumor compared to adjacent cells. This work showed for the first time that the overexpression of VISTA in breast cancer cells is associated with the EMT process. Moreover, a positive correlation between VISTA and PD1 was also identified. These results highlighted the immunosuppressive effect of VISTA in breast cancer patients and indicated that bi-specific targeting of VISTA and PD1 in combination therapy could be beneficial for these patients.